Perancangan UI/UX Aplikasi Ngaji Ummi Berbasis Mobile Menggunakan Metode Design Thinking - Khasanah, Afifa Nur; Resmi, Mochzen Gito; Hermanto, Teguh Iman (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Muslims occupy first place in Indonesia. There are 223 million Indonesian Muslims spread throughout the archipelago, among them there are 153.8 million or around 65% of the Indonesian Muslim population who cannot read the Qur'an, this is a matter of concern for the Indonesian Muslim population in learning the Qur'an. Many factors that affect people are difficult to learn the reading of the Qur'an, and from various observations, the Ummi method is applied as a method that is easy to apply and is a method that is starting to be widely used today. The current technological developments certainly support the ease of learning the Ummi method anywhere, anytime, and by anyone. An important factor of mobile applications is the user interface to provide convenience and comfort for application users. The design thinking method is used in this research, this method solves problems by approaching users, there are 5 stages in this method: The mobile application prototype produced in this study is called "Ngaji Ummi", and testing is carried out using the system usability scale method. The average SUS value obtained is 81.071, it can be concluded that the "Ngaji Ummi" application meets the acceptable category or can be accepted by users. With the "Ngaji Ummi" mobile application, it is hoped that it will help the community to learn the Qur'an easily and pleasantly.Keywords – Al-Qur’an, Ummi Method, Ngaji Ummi, Design Thinking, System Usability Scale.